2006
DOI: 10.1002/uog.2672
|View full text |Cite
|
Sign up to set email alerts
|

Normal fetal lung volume measured with three-dimensional ultrasound

Abstract: Objectives To construct reference intervals for fetal lung volumes measured longitudinally using three-dimensional (3D)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
3
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 47 publications
(114 reference statements)
9
49
3
5
Order By: Relevance
“…Again, for either volumetric method, the actually measured volume should be expressed as a function of what is expected for an appropriate normal match still using the same measuring method. Several groups have published nomograms for multiplanar or rotational volume 3D US acquisitions in normal pregnancies [7][8][9][10][11][12][13][14][15] .…”
Section: Imaging the Normal Fetal Lungmentioning
confidence: 99%
“…Again, for either volumetric method, the actually measured volume should be expressed as a function of what is expected for an appropriate normal match still using the same measuring method. Several groups have published nomograms for multiplanar or rotational volume 3D US acquisitions in normal pregnancies [7][8][9][10][11][12][13][14][15] .…”
Section: Imaging the Normal Fetal Lungmentioning
confidence: 99%
“…[88][89][90][91][92] Recently, Gerards et al reported excellent agreement between 3DUS lung volume measurements and magnetic resonance imaging (MRI). 88,[91][92][93] In addition, numerous reports suggest the measurement is highly reproducible.…”
Section: Lung Volumesmentioning
confidence: 95%
“…[88][89][90][91][92] Recently, Gerards et al reported excellent agreement between 3DUS lung volume measurements and magnetic resonance imaging (MRI). 88,[91][92][93] In addition, numerous reports suggest the measurement is highly reproducible. [88][89][90][91][92] In 2006 Wladimiroff et al 94 proposed the use of 3DUS lung volume measurements for prediction of lung hypoplasia.…”
Section: Lung Volumesmentioning
confidence: 95%
See 1 more Smart Citation
“…Fetal lung volumetry, in normal and high-risk conditions for pulmonary hypoplasia, has been obtained with both the multiplanar and VOCAL methods (Gerards et al 2006;Ruano et al 2006b), even though VOCAL has several advantages over the multiplanar method. These consist of the ability to include smaller portions of the lungs extending below the dome of the diaphragm and the possibility of modifying the contour along each plane (Peralta et al 2006).…”
Section: -Dus In Assessment Of Fetal Organ Volume and Estimation Of mentioning
confidence: 98%